DEVELOPMENT OF COMPLEX TECHNOLOGIES FOR PROCESSING OF RICE BRAN WITH OBTAINING OF THERAPEUTIC OIL AND MEDICINE – PHYTIN - R. S., Tashmenov; G.E., Orymbetova; Zh. U., Myrkhalykov; Gao, Enjun; Z.M., Shakiryanova (European Scientific Journal, ESJ, 2015)
In this article, showed effectiveness of obtaining therapeutic, edible oil and medicine-phytin and researched the viability of using waste generated during processing of rice - rice bran. Carried out research on the qualitative and physical - chemical characteristics of rice bran and defined quantitative content of phytin in raw materials and substances.